Review: The association between anxiety and poor attendance at school – a systematic review. Issue 3 (27th February 2019) - Finning, Katie; Ukoumunne, Obioha C.; Ford, Tamsin; Danielson‐Waters, Emilia; Shaw, Liz; Romero De Jager, Ingrid; Stentiford, Lauren; Moore, Darren A.
Abstract : Background: Anxiety may be associated with poor attendance at school, which can lead to a range of adverse outcomes. We systematically reviewed the evidence for an association between anxiety and poor school attendance. Methods: Seven electronic databases were searched for quantitative studies that reported an estimate of association between anxiety and school attendance. Anxiety had to be assessed via standardised diagnostic measure or validated scale. Articles were screened independently by two reviewers. Meta‐analyses were performed where possible, otherwise results were synthesised narratively. Results: A total of 4930 articles were screened. Eleven studies from six countries across North America, Europe and Asia, were included. School attendance was categorised into: (a) absenteeism (i.e. total absences), (b) excused/medical absences, (c) unexcused absences/truancy and (d) school refusal. Findings from eight studies suggested associations between truancy and any anxiety disorder, as well as social and generalised anxiety. Results also suggested cross‐sectional associations between school refusal and separation, generalised and social anxiety disorders, as well as simple phobia. Few studies investigated associations with absenteeism or excused/medical absences. Conclusions: Findings suggest associations between anxiety and unexcused absences/truancy, and school refusal. Clinicians should consider the possibility of anxiety in children and adolescents with poor attendance. However, there is a lack of high quality evidence, little longitudinal research and limited evidence relating to overall absenteeism or excused/medical absences, despite the latter being the most common type of absence. These gaps should be a key priority for future research.